The Role of Hollywood Figures in Propagating Transnational Movement: Case Study of #MeToo in South Korea (2017– 2019) - Alfaqah Dwi; Witri Elvianti (President University, 2022)
Sexual misconduct in South Korea occurs in various forms and in various sectors since a long time due to the social construction of the local citizen. Series of sexual harassment cases that take place in the United States’ film industry which made Hollywood figures raise their voices succeeded in forming a transnational movement called the #MeToo Movement. This article will explain the role of celebrities in pioneering the transnational movement with a case study of the #MeToo movement in South Korea in the period 2017 – 2019. In investigating the role of Hollywood figures, the author uses qualitative research methods referring to the actions of Hollywood figures correlated with the theory of Transnational Advocacy Network and Popular Culture. This research discovers that public figures have motivated victims of sexual harassment to speak up which attracted global attention and ultimately succeeded in making legislative reforms in various countries.